Shooting for a century the India-Pakistan conundrum - Cohen, Stephen P., 1936- (Brookings Institution Press, 2013)
"Examines the antagonistic relationship between India and Pakistan and the territorial and identity issues that have divided them for sixty-five years, and possibly the next thirty-five, and offers ways the tension between the two might be ameliorated if not solved, including a more active role for the United States"--Provided by publisher.